PENGAWASAN PEMERINTAH TERHADAP PELAKSANAAN PROGRAM PEMBAGIAAN ALAT TANGKAP DI KECAMATAN BISSAPPU KABUPATEN BANTAENG - Jufri Jufri; Alimuddin Said; Samsir Rahim (Kolaborasi : Jurnal Administrasi Publik, 2018)
The purpose of this was to find out how the geverment supervision on the implementation of fishing gear program in Bissappu district Bantaeng regency as well as to know the factors that influenced the supervision of the implementation in the district. Type of research was qualitative. This study used case study type. Date collection techiniques used in the form of questionnaires. Observation and documentation. The result of this study indicated that the supervision carried ouy by the geverment was monitoring and controlling and there was aa significant influence between the government supervision on the program of distribution of fishing gear in Bissappu District Bantaeng regency. Goverment supervion was strongly influenced by leadership, effectiveness and welfare. Keywords: Government Supervision, Community Empowerment, and Welfare